The roots of bioethics health, progress, technology, death - Callahan, Daniel, 1930- (Oxford : Oxford University Press, 2012)
Daniel Callahan's life time work in bioethics has again and again returned to the root problems of health, progress technology, and death. How we think about each of them individually and in relation to each other will shape the way we approach and deal with the most common dilemmas of modern medicine. They are at the roots of the field.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Bioethics